2006
DOI: 10.1002/da.20134
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment and suicidal behavior in severe depression: ECT and antidepressant pharmacotherapy may have different effects on the occurrence and seriousness of suicide attempts

Abstract: Our objective in this article is to assess the relation between long-term treatments of depressive episodes and attempted or completed suicide in patients who had had a severe depression at index admission. A blind record evaluation of 96 suicides with a primary severe depression and matched controls has been performed. Out of those, 57 and 33, respectively, had made suicide attempts. Occurrence of attempt was less common after electroconvulsive therapy (ECT). However, seriousness of suicide attempt appeared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Adequate treatment of depressive episodes with antidepressant pharmacotherapy and ECT was similar throughout the course of depression in suicides and controls and so was improvement, as has been described in a previous paper (Brådvik & Berglund, 2006). There were also similar low rates of Lithium treatment, mainly for bipolar I.…”
Section: Course Of Depressionsupporting
confidence: 55%
“…Adequate treatment of depressive episodes with antidepressant pharmacotherapy and ECT was similar throughout the course of depression in suicides and controls and so was improvement, as has been described in a previous paper (Brådvik & Berglund, 2006). There were also similar low rates of Lithium treatment, mainly for bipolar I.…”
Section: Course Of Depressionsupporting
confidence: 55%
“…It may be a coincidence, but it could also indicate an effect of ECT on suicidality. 30 We need further studies on the effect of different regimens of combined pharmacotherapy and ECT on the risk for suicide attempts and suicide, including the benefit and risks of lithium therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent study, the same researchers also found that while suicide attempts were, overall, less frequent after ECT than after antidepressant drugs, there were significantly more severe suicide attempts (defined as highly lethal suicide attempts, (i.e. requiring intensive care) following ECT than following antidepressants (Bradvik & Berglund, 2006).…”
Section: Does Ect Prevent Suicide?mentioning
confidence: 93%